Comparison and Functional Analysis of Chemosensory Protein Genes From Eucryptorrhynchus scrobiculatus Motschulsky and Eucryptorrhynchus brandti Harold - Wang, Qian; Wen, Xiaojian; Lu, Yi; Wen, Junbao (Frontiers in Physiology, 2021)
The tree-of-heaven root weevil Eucryptorrhynchus scrobiculatus and the tree-of-heaven trunk weevil E. brandti are closely related species monophagously feeding on the same host plant Ailanthus altissima (Mill) Swingle of different positions. However, the mechanisms of how they selected the different parts of host tree are unclear. As chemosensory systems playing important roles of host-location and oviposition, we screened candidate chemosensory protein genes of the two weevils from their transcriptomes of different developmental stages for signal molecule-binding analysis and difference comparison. In this study, we identified 12 candidate chemosensory proteins (CSPs) of E. scrobiculatus and E. brandti, respectively. The qRT-PCR results showed that EscrCSP7/8a/9 and EbraCSP7/8/9 were significantly expressed in adult antennae, while EscrCSP8a and EbraCSP8 share low sequences identity suggesting that they may respond to different odorant molecule-binding. Besides, EbraCSP6 and EscrCSP6 were mainly expressed in antennae and proboscises, probably participate in the process of chemoreception. The binding simulation of nine volatile compounds of the host plant to EscrCSP8a and EbraCSP8 intimate that (1R)-(+)-Alpha-Pinene, (-)-Beta-Caryophyllene and Beta-Elemen show higher binding affinities with EscrCSP8a but lower with EbraCSP8. In addition, there were 7, 2, and 1 EbraCSPs mainly expressed in pupae, larvae and eggs, respectively, indicating possible developmental-related roles in E. brandti. We screened out several olfactory-related possible CSP genes in E. brandti and E. scrobiculatus, analyzed the binding systems of CSPs with different compounds, providing a basis for explaining the niches differentiation of the two weevils.